Investigations of thermoluminescent silica beads of different manufacturers and colours. (February 2019) - Ley, K.; Jafari, S.M.; Lohstroh, A.; Bradley, D.A.
Abstract: Increased interest in silica based materials for use in medical thermoluminescence (TL)-based dosimetry has led to investigations of tailoring different types of technologies for specific uses. Here we study a low-cost approach to the harnessing of this emerging dosimetry technique, utilising commercially manufactured doped silica beads. The beads have been previously studied using two well-established TLD Reader systems, namely the HARSHAW and TOLEDO brands, and are now being studied making use of a Ris ø TL/OSL system, a more modern and also highly sensitive facility. Characterisation studies have been conducted and results from this have been compared against that of existing literature including glow-curves and colour study TL-yield responses. The outcome confirms that colourless beads produce the highest yield when observing the 2.7 eV electron trap of silica based materials with TLD techniques. Investigations have also been made concerning the batch homogeneity of coloured beads from two different manufacturers, Mill Hill, Japan and Toho Czech, and different physical finishes of the silica beads, transparent or frosted. Studies also show that the colourless beads displaying the best batch homogeneity overall are those produced by Mill Hill Japan, measured by the percentage difference from the average TL yield, with the clear petite beads displaying the best homogeneity. Abstract : Highlights: A range of different coloured silica beads with different finishes irradiated and the TL yield measured. Comparison has been made between the bead manufacturers, Toho (Czech Republic) and Mill Hill (Japan). Greatest TL produced from colourless beads while blue and green beads generally showed low yields. Peak of glow-curve varies with bead colour and manufacturer.